Faktor yang Berhubungan Dengan Kerusakan Berkas Rekam Medis di Rumah Sakit Umum Bandung - Sembiring, Rima Melinda; Tarigan, Andini Mentari; Rangkuti, Dyna Safitri Rakhelmi; Sianturi, Greisella A. (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Damage to medical record documents represents a serious challenge in hospital archive management, characterized by torn, faded, discolored, or illegible documents due to intrinsic (material quality) and extrinsic (environmental) factors. A preliminary survey at Bandung Medan General Hospital identified 47 damaged documents in September 2024, indicating the need for systematic intervention. Objective: To analyze the relationship between intrinsic and extrinsic factors and damage to medical record files at Bandung Medan General Hospital. Methods: This study employed a cross-sectional analytical design with a sample of 92 documents (purposive sampling). Data were analyzed using univariate and bivariate (Chi-Square test) methods. Results: The findings revealed that 51.1% of documents were damaged, with intrinsic factors (paper quality, ink, and adhesives) identified in 47 documents (51.1%) and extrinsic factors (physical, biological, and chemical environment) in 48 documents (52.2%). Statistical analysis demonstrated a highly significant association between intrinsic factors and document damage (p=0.000; OR=15.2), indicating documents with material quality issues had a 15 times higher risk of damage. Similarly, extrinsic factors showed a highly significant relationship (p=0.000; OR=12.8), with suboptimal storage conditions being the primary contributor. Environmental factors, particularly high humidity (78%) and dust accumulation (65%), were the most dominant causes of physical document damage. Conclusion: Medical record damage is influenced by both factors, with recommendations for storage system improvements, environmental control, and implementation of standard operating procedures (SOPs) for risk mitigation. The study findings should serve as valuable input for enhancing medical record document storage to ensure better safety and preservation.